The use of solid state NMR to characterize high density polyethylene/organoclay nanocomposites - Rodrigues, Tathiane; Tavares, Maria I.B.; Soares, Igor; Moreira, Ana; Ferreira, Antonio (Publishing House of Lviv Polytechnic National University, 2009)
Recently the development of new materials, in special polymeric nanocomposites, formed by polymer and layered silicates, have gained attention. In this work nanocomposites based on high-density polyethylene matrix (HDPE) and organically modified clay were prepared by melt processing and characterized by the determination of proton spin-lattice relaxation time through solid state nuclear magnetic resonance (NMR) spectroscopy. This work has a proposal to add one quantitative technique to help the researchers to better evaluate polymeric nanocomposite, because NMR is an important tool employed to study both molecular structure and dynamic molecular behavior. The nanocomposites were mixed in a twin-screw extruder, varying the shear rate parameter: 60 and 90 rpm at 463 K. Nanocomposites obtained were characterized through Xray diffraction; thermal analysis; impact resistance and nuclear magnetic resonance. The T1H results showed that the samples present different molecular domains according to the clay dispersion, forming an intercalated and/or exfoliated nanocomposites. The measurement of relaxation time, using low field NMR, is a useful method to evaluate changes in the molecular mobility of nanocomposite and can inferwhether the sample is exfoliated and/or intercalated, since lamellar filler is used. Плавленням поліетилену високої густини як матриці та органічно модифікованої глини були приготовлені нанокомпозити та дано їх характеристику внаслідок визначення часу релаксації спін-граткового протону, використовуючи ЯМР-спектроскопію твердого тіла. В роботі запропоновано використовувати цю якісну характеристику для кращого оцінювання полімерного нанокомпозиту, оскільки ЯМР-спектроскопія є важливим методом вивчення одночасно молекулярної структури та динамічної молекулярної поведінки. Нанокомпозити готували перемішуванням при 463 К у двошнековому екструдері зі швидкістю 60 і 90 об/хв. Отримані нанокомпозити були охарактеризовані з використанням рентген-дифракції, термічного аналізу, міцності до удару і ядерного магнітного резонансу. Т1Н результати показали, що зразки містять різні молекулярні домени диспергованої глини, утворюючи включені і/або розшаровані нанокомпозити. Вимірювання тривалості релаксації, використовуючи ЯМР слабкого поля (низької області), є придатним методом оцінювання змін в молекулярній мобільності нанокомпозиту і дає можливість визначити тип нанокомпозиту.
Використання ЯМР твердого тіла для характеристики поліетилен високої густини/глино-органічних нанокомпозитів
Keywords: nanocomposites; low field NMR; high-density polyethylene matrix; clay; нанокомпозити; ЯМР слабкого поля; поліетиленова матриця великої густини; глина